Amylolytic Enzymes Acquired from L-Lactic Acid Producing Enterococcus faecium K-1 and Improvement of Direct Lactic Acid Production from Cassava Starch - Kridsada Unban (2018)
© 2017, Springer Science+Business Media New York. An amylolytic lactic acid bacterium isolate K-1 was isolated from the wastewater of a cassava starch manufacturing factory and identified as Entercoccus faecium based on 16S rRNA gene sequence analysis. An extracellular α-amylase was purified to homogeneity and the molecular weight of the purified enzyme was approximately 112 kDa with optimal pH value and temperature measured of 7.0 and 40 °C, respectively. It was stable at a pH range of 6.0–7.0, but was markedly sensitive to high temperatures and low pH conditions, even at a pH value of 5. Ba 2+ , Al 3+ , and Co 2+ activated enzyme activity. This bacterium was capable of producing 99.2% high optically pure L-lactic acid of 4.3 and 8.2 g/L under uncontrolled and controlled pH at 6.5 conditions, respectively, in the MRS broth containing 10 g/L cassava starch as the sole carbon source when cultivated at 37 °C for 48 h. A control pH condition of 6.5 improved and stabilized the yield of L-lactic acid production directly from starch even at a high concentration of starch at up to 150 g/L. This paper is the first report describing the properties of purified α-amylase from E. faecium. Additionally, pullulanase and cyclodextrinase activities were also firstly recorded from E. faecium K-1.